Introduction - Helge Hvid (Nordic Journal of Working Life Studies, 2016)
In this issue, two of the articles present studies on the creation of working conditions through work place communication—informal communication at the workplace  and at formal meetings, respectively. An article examines how young unemployed people position themselves in relation to the dominant discourse on unemployment. An article examines the impact of collective agreements on the employment of older workers, and finally, an article presents a study on employment in the third sector (...)